Advances in image and graphics technologies : 11th Chinese Conference, IGTA 2016, Beijing, China, June 19-20, 2015, Proceedings /: 11th Chinese Conference, IGTA 2016, Beijing, China, June 19-20, 2015, Proceedings. (2016) - Unknown
No abstract available